Politik Hukum Pembentukan Peraturan Daerah Provinsi Dikaitkan dengan Kewenangan Menteri Dalam Negeri dalam Pembatalan Peraturan Daerah Provinsi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The issuance of the Constitutional Court Decision number 56 / PUU-XIV / 2016 related to thecancellation of the regional regulation by the governor and minister. With the Constitutional Court's decision,the Minister of Home Affairs will no longer be able to revoke the provincial regulation. In the decision also theConstitutional Court stated, for the sake of legal certainty and in accordance with the 1945 Constitution of theRepublic of Indonesia according to the Court, the testing or cancellation of regional regulations became thedomain of the constitutional authority of the Supreme Court. Meanwhile, in carrying out the judicial review, theproblems faced included, among others, the mechanism that made it difficult for the community to take theprocedure to file a judicial review of the local regulation. On the other hand the Minister of Home Affairsobtained the authority to carry out executive review on the basis of the authority granted by the RegionalGovernment Law and its derivative legislation in carrying out guidance and supervision on the implementationof regional autonomy, in this case the regional regulation. So that it has implications for legal uncertainty inlaw enforcement and development in Indonesia, especially those related to whether the regulation has legalstrength or lacks legal force in its implementation, especially the provincial regulations that are passed on bythe minister of interior in 2016. There are two things from the problem research principal that can beconcluded. First, the legal politics of the establishment of provincial regulations associated with the authorityof the Minister of Home Affairs in the cancellation of 2016 regional regulations which have implications forlegal uncertainty in testing local regulations with the legal dualism between the existence of judicial review andexecutive review in the perspective of applicable legislation can cause problems . Secondly, the ideal idea in theFormation of Provincial Regulations is to provide ideas in the propemperda process so that they are inaccordance with the concept of the desired legal requirements.This This type of research is normative legal research, because in this study the author conducted astudy of legal norms, by first identifying the legal principles that have been formulated in certain laws andregulations, in order to provide an explanation of the qualitative juridical is a research procedure thatproduces descriptive analytical data, which collects all data from primary and secondary legal materialsrelating to the politics of cancellation of provincial regulations by accommodating legal theories and otherlegislation. Accompanied by data sources used in this study include: primary data, secondary data and tertiarydata.The author's suggestion, First, seeks to improve the mechanism of local regulation testing. Secondly, thelegislators should need systematic and continuous efforts to improve the capacity of DPRD members and LGsin designing good local regulations.Keywords: Establishment of Regional Regulations-Politics Law-Regional Autonomy